Patient Unique Stigmatization Holistic tool in dermatology (PUSH‐D): Development and validation of a dermatology‐specific stigmatization assessment tool. (25th October 2022) - Ezzedine, Khaled; Shourick, Jason; Bergqvist, Christina; Misery, Laurent; Chuberre, Bertrand; Kerob, Delphine; Halioua, Bruno; Le Fur, Gaëlle; Paul, Carle; Richard, Marie‐Aleth; Taieb, Charles
Abstract: Background: The skin plays an important role in establishing interpersonal relationships, and thus visible skin disorders, which have a significant impact on physical appearance, influence other people's behaviours and attitudes. Objective: To develop and validate a dermatologic‐specific questionnaire to evaluate stigmatization in individuals with visible skin conditions. Methods: Items were generated by a verbatim report based on qualitative interviews with patients with various dermatologic conditions. Subsequently, a study was implemented for psychometric analysis. A dermatology‐specific stigmatization questionnaire (PUSH‐D) was refined via item reduction according to inter‐question correlations, consensus among experts and exploratory factor analysis. Internal consistency was determined by calculating Cronbach's α. Concurrent validity was determined by calculating the correlation between PUSH‐D and the Dermatology Life Quality Index (DLQI) and the Rosenberg Self‐Esteem Scale (RSES). Results: From a primary list of 22 items, PUSH‐D was reduced to a 17‐item questionnaire, covering two pertinent dimensions based on the exploratory factor analysis. Construct validity was demonstrated, and PUSH‐D showed good internal consistency (Cronbach's α = 0.9). PUSH‐D correlated strongly with the DLQI 0.72 ( p  < 0.001) and moderately with the RSES 0.49 ( p  < 0.001). Conclusion: PUSH‐D allows a comprehensive view of the degree of stigmatization in visible skin disorders, as well as the comparability of stigmatization levels across various skin conditions.